I$1 (Bm mighty! s - McMullan, Kate.; McMullan, Jim, 1936- (New York : Joanna Cotler Books, 2003)
A little tugboat shows how he can bring big ships into the harbor even though he is small.
Keywords: Tugboats -- Fiction; Size -- Fiction; Ships -- Fiction